2017
DOI: 10.1016/j.bcmd.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and macrovascular function in children with sickle cell anaemia and sickle cell haemoglobin C disease

Abstract: It is unclear whether vascular function is affected similarly in children with sickle cell anaemia (SS) and children with sickle haemoglobin C (SC) disease. Therefore, we compared micro and macrovascular functions in healthy (AA) children, children with SS and SC disease, and assessed their association with physical activity. Participants (24 SS, 22 SC and 16 AA), were compared in terms of 1) thermal hyperaemic response (finger pad warming to 42°C) measured by Laser Doppler techniques, 2) arterial stiffness de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…CR-PWV was measured in a cohort of 24 SCA patients, and compared to a group of AA (n = 16) of the same ethnic origin. As previously reported ( 21 ), PWV was higher in SCA than in AA ( Figure 3C , p < 0.01), indicating increased arterial stiffness in the former group. Circulating RBC-MPs were also measured in 24 patients of this cohort to test the association with the carotid-radial PWV.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…CR-PWV was measured in a cohort of 24 SCA patients, and compared to a group of AA (n = 16) of the same ethnic origin. As previously reported ( 21 ), PWV was higher in SCA than in AA ( Figure 3C , p < 0.01), indicating increased arterial stiffness in the former group. Circulating RBC-MPs were also measured in 24 patients of this cohort to test the association with the carotid-radial PWV.…”
Section: Resultssupporting
confidence: 89%
“…Arterial stiffness is considered to be a relevant indicator of macrovascular function ( 20 ), and is increased in patients with SCA ( 21 ). We evaluated arterial stiffness by measuring carotid-radial pulse wave velocity (CR-PWV) with a non-invasive automated device (SphygmoCor System, Actor, Sydney, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This oxidative milieu results in exacerbated NO scavenging via an oxygen free radicaldependent mechanism, and further affects the vascular system. Mockesch et al (20) recently showed that the impairment of microvascular regulation in children with SCD was significantly associated with both nitrotyrosine and markers of systemic oxidative stress, confirming the important roles of oxidative stress and NO scavenging in the development of vascular dysfunction in SCD.…”
Section: Hemolysis Oxidative Stress and Inflammationmentioning
confidence: 86%
“…Belhassen et al (19) reported increased diameter in the brachial artery at baseline in SCD patients, compared to a control group, but the vessel was not able to further dilate in response to a flow-mediated dilation procedure. At the microcirculatory level, Moeckesch et al (20) reported decreased hyperemic response to skin heating localized stress in children with SCD, compared to healthy children, suggesting impaired microcirculatory NO-driven vasodilation in the former population.…”
Section: Hemolysis and Nitric Oxide (No) Bioavailabilitymentioning
confidence: 99%